Pengaruh Desain Pada Kesakralan Masjid - Hasbi, Rahil Muhammad; Musdinar, Inggit (Universitas muhammadiyah palembang, 2020)
The Mosque is considered as the House of Almighty, Allah SWT, and also a place of worship for Muslims; doing salat, pray, reciting Quran, etc. When doing salat or praying, Muslims need to focus and concentrate, therefore they need a serene atmosphere that can support to focus and concentrate when they are doing the salat or praying and other activities. This condition can happen if the mosque produces a sacred atmosphere.Understanding the meaning of the sacred can vary in each individual. Each individual has her/his way to understand the meaning of sacredness. These differences emerge because of many factors which can influence the meaning of sacredness in a mosque. Therefore this study wants to find out what factors can influence the sacredness of a mosque and whether mosque design is one of the factors which have greatly influenced the sacredness of a mosqueThe research method is a qualitative method using grounded theory. The results of the study stated that the design was the most chosen factor by respondents as a factor influencing the sacredness of the mosque